A Comprehensive Study on Parametric Effects and Optimization Strategies in Non-Conventional Machining of MMCs (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Metal Matrix Composites (MMCs) are extensively used in advanced engineering applications due to their superior mechanical and thermal properties; however, the presence of hard reinforcements makes their machining challenging using conventional methods. Non-conventional machining (NCM) processes such as Electrical Discharge Machining (EDM), Wire EDM, Abrasive Water Jet Machining (AWJM), Ultrasonic Machining (USM), and Laser Beam Machining (LBM) have therefore gained significant attention for effective machining of MMCs. This paper presents a comprehensive study on the effects of key process parameters—including discharge current, pulse duration, voltage, abrasive flow rate, jet pressure, stand-off distance, and tool vibration—on machining performance characteristics such as material removal rate, surface roughness, tool wear rate, kerf width, and heat-affected zone. In addition, various single- and multi-objective optimization strategies, including Taguchi-based approaches, Response Surface Methodology, Grey Relational Analysis, evolutionary algorithms, and hybrid techniques, are critically reviewed and compared. The study identifies optimal parametric combinations, highlights trade-offs between productivity and surface integrity, and discusses existing challenges and future research directions, thereby providing valuable insights for enhancing the machining efficiency and quality of MMCs using non-conventional processes.